Peran Etika Bisnis dalam Meningkatkan Tanggung Jawab Sosial Perusahaan - Uswatun Hasanah; Mulia A Sura; Riswan Rambe (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The lack of integration of ethical principles into corporate social responsibility (CSR) practices remains a common issue, posing significant challenges in building public trust and ensuring business sustainability. This study aims to examine how the implementation of business ethics can enhance the effectiveness of CSR within corporate environments. The research employs a literature review method, analyzing various academic publications, regulatory frameworks, and corporate reports relevant to business ethics and CSR. The findings reveal that consistent application of ethical values can deepen the meaning and impact of CSR initiatives, improve corporate reputation, and strengthen relationships with stakeholders in a more meaningful and sustainable manner.Nevertheless, several challenges persist, particularly in the form of organizational cultural differences and the suboptimal internalization of ethical principles into corporate systems and work culture. Therefore, strategic efforts are required to ensure that business ethics are not merely treated as normative concepts, but are truly embraced as core values in CSR practices aimed at achieving social and environmental sustainability.